Buckling restrained braced frame seismic response for far-field, near-field, and long-duration earthquakes. (December 2022) - Ahmad, Fokruddin; Phillips, Adam
Abstract: This paper presents the structural response of prescriptively designed buckling restrained braced frame buildings to four ground motion sets with different fault characteristics. The four ground motion sets are characteristic of far field, near field with pulse, near field with no pulse, and subduction zone long duration earthquakes. Two prototype buildings of different heights were used for the analysis and designed for a site in Seattle, WA. The analysis was conducted using three-dimensional numerical models of the prototype buildings developed in OpenSeesPy. The simulated buckling restrained brace response was validated with three experimental tests from the literature. The analysis results were used to investigate the effect of ground motion type on the structural response parameters of inter story drift, peak floor velocity, peak floor acceleration, residual inter story drift, and cumulative ductility demand. Results show that the near field motions increase the inter story drift demand compared to far field and long duration motions. All motion sets were likely to cause some level of structural and non-structural damage to drift, velocity, and acceleration sensitive components at the DE and MCER hazard levels, but severe damage states may not be highly likely. The median residual inter story drift was less than 0.5% for all motion sets. The cumulative ductility demand of the subduction zone long duration motion set was 5 to 6 times greater than that of the far field or near field motion sets and exceeded the code-minimum cumulative ductility for prequalification for upwards of 60% of the analyses. Highlights: Study results confirm that near-field earthquakes result in large story drift than far-field earthquakes. Code-designed BRBFs are likely to have low levels of nonstructural damage. Code-designed BRBFs are unlikely to have severe levels of nonstructural damage. Long-duration earthquakes result in 5–6 times more cumulative ductility demand than near-field or far-field earthquakes. Long-duration earthquakes have cumulative ductility demand in excess of minimum code requirements for pre-qualified BRBs.